Assessing the integration of disaster education in the Merdeka curriculum: A case study from students perspectives in Banda Aceh, Indonesia - Najahi, Rosikhotun; Reza, Muhammad; Diana, Nasri; Alkhaira, Fathin; Nurdin, Nurmalahayati (TDMRC, Universitas Syiah Kuala, 2025)
This study highlights the importance of integrating disaster education into schools to improve students' awareness of disaster risks. Indonesia, which is vulnerable to natural hazards, has been working to incorporate disaster-related content into its education system. This research assesses the extent to which disaster knowledge has been integrated into the Merdeka Curriculum from the students perspectives. Given Indonesias rapid curriculum changes and shifting priorities, there is concern that disaster education may be overlooked. The study employed a mixed-method approach, combining content analysis of the curriculum with a student survey. The content analysis reviewed curriculum documents to examine how disaster topics were integrated across subjects. The survey, conducted among middle school students in Banda Acehan area prone to disasterscaptured students experiences learning about disasters both inside and outside the classroom. A total of 267 students from the Banda Aceh area participated in the study.Results show that disaster knowledge is included in subjects such as Bahasa Indonesia, Chemistry, Biology, Geography, and Mathematics. Students also participate in experiential activities such as museum visits and disaster site tours, which deepen their understanding. Overall, the findings suggest that the interdisciplinary and experiential approach of the Merdeka Curriculum effectively promotes disaster literacy, helping students become more aware of and prepared for natural hazards. Despite curriculum challenges, Indonesias efforts support disaster education and resilience-building among young learners.